Unorthodox lawmaking : new legislative processes in the U.S. Congress - Sinclair, Barbara (New Delhi, 2017)
Unorthodox Lawmaking introduces students to the intricacies of Congress while also providing the tools to assess the relative successes and limitations of the legislative process. It explores the full range of special procedures and processes that make up the legislative process, as well as the reasons these unconventional routes evolved. New coverage also includes changes to the filibuster rules under Harry Reid, and the fiscal cliff and government shutdowns.
Keywords: Politics and government